2005
DOI: 10.1164/rccm.200409-1222oc
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Oxidative Stress and Free-Radical Activity in Serum from Asymptomatic Shipyard Welders

Abstract: These results document that exposure to welding can cause changes in serum biomarkers of oxidative stress that may be valuable in clinical monitoring of disease development and in assessing whether further reduction of worker exposures is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 52 publications
5
59
1
1
Order By: Relevance
“…Human studies related to welding fume exposure and immune function. Author Finding Avashia et al (2007) Fatal pneumonia case in male metalworkers in Texas Beaumont and Weiss (1980) Excess mortality from pneumonia with welding fume exposure Borska et al (2003) Alterations of systemic immunologic proteins Boshnakova et al (1989) Suppression of T-and B-lymphocyte immune system Coggon et al (1994) Pneumococcal and unspecified lobar pneumonia in metal workers Comhair and Erzurum (2002) Welding fume exposure associated with systemic inflammation and/or oxidative stress du Plessis et al (2010) Welding fume exposure associated with systemic inflammation and/or oxidative stress Fang et al (2009) Welding fume exposure associated with systemic inflammation and/or oxidative stress Registrar General (1958,1971,1981) Welders have increased mortality from pneumonia Han et al (2005) Welding fume exposure associated with systemic inflammation and/or oxidative stress Hanovcova et al (1998) Alterations of systemic immunologic proteins Hoffmaster et al (2004) Non-fatal case of pneumonia in a male metalworker in Louisiana Kim et al (2005) Welding fume exposure associated with acute systemic inflammation and/or oxidative stress McMillan and Pethybridge (1983) Mortality from pneumonia with welding fume exposure Milham (1983) Mortality from pneumonia with welding fume exposure Miller et al (1997) Fatal pneumonia case of two male metalworkers in Louisiana Nakata et al (2006) Inverse relationship between blood manganese levels and lymphocyte populations Newhouse et al (1985) Mortality from pneumonia with welding fume exposure Nielsen et al (1993) Alterations of systemic immunologic proteins Palmer et al (2003) Inhalation of metal fumes renders the worker susceptible to infectious pneumonia Palmer et al (2006) Chronic metal fume exposure impairs lung defenses Polednak (1981) Mortality from pneumonia with welding fume exposure Puntoni et al (1979) Mortality from pneumonia with welding fume exposure Tuschl et al (1997) Welding fume reduced the cytotoxic activity of lymphokine-activated killer cells functionality of immune competent cells was associated with altered immune-related cytokine and antibody production as well as impaired resolution...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human studies related to welding fume exposure and immune function. Author Finding Avashia et al (2007) Fatal pneumonia case in male metalworkers in Texas Beaumont and Weiss (1980) Excess mortality from pneumonia with welding fume exposure Borska et al (2003) Alterations of systemic immunologic proteins Boshnakova et al (1989) Suppression of T-and B-lymphocyte immune system Coggon et al (1994) Pneumococcal and unspecified lobar pneumonia in metal workers Comhair and Erzurum (2002) Welding fume exposure associated with systemic inflammation and/or oxidative stress du Plessis et al (2010) Welding fume exposure associated with systemic inflammation and/or oxidative stress Fang et al (2009) Welding fume exposure associated with systemic inflammation and/or oxidative stress Registrar General (1958,1971,1981) Welders have increased mortality from pneumonia Han et al (2005) Welding fume exposure associated with systemic inflammation and/or oxidative stress Hanovcova et al (1998) Alterations of systemic immunologic proteins Hoffmaster et al (2004) Non-fatal case of pneumonia in a male metalworker in Louisiana Kim et al (2005) Welding fume exposure associated with acute systemic inflammation and/or oxidative stress McMillan and Pethybridge (1983) Mortality from pneumonia with welding fume exposure Milham (1983) Mortality from pneumonia with welding fume exposure Miller et al (1997) Fatal pneumonia case of two male metalworkers in Louisiana Nakata et al (2006) Inverse relationship between blood manganese levels and lymphocyte populations Newhouse et al (1985) Mortality from pneumonia with welding fume exposure Nielsen et al (1993) Alterations of systemic immunologic proteins Palmer et al (2003) Inhalation of metal fumes renders the worker susceptible to infectious pneumonia Palmer et al (2006) Chronic metal fume exposure impairs lung defenses Polednak (1981) Mortality from pneumonia with welding fume exposure Puntoni et al (1979) Mortality from pneumonia with welding fume exposure Tuschl et al (1997) Welding fume reduced the cytotoxic activity of lymphokine-activated killer cells functionality of immune competent cells was associated with altered immune-related cytokine and antibody production as well as impaired resolution...…”
Section: Discussionmentioning
confidence: 99%
“…In a 3-year study by Hanovcova et al (1998), increased lymphocyte counts, T-lymphocyte percentages, leukocyte metabolism, and decreased phagocytosis were found in SS welders (n = 22-53) compared to a standard laboratory reference value/non-exposed persons from the same plant. Exposure to metal fumes has been shown to induce systemic inflammation and oxidative stress parameters in the serum of welders, which could potentially lead to immune effects (Comhair and Erzurum, 2002;Han et al, 2005;Kim et al, 2005;Fang et al, 2009). A recent study by du Plessis et al (2010) measured the oxidative status of peripheral blood mononuclear cells in welders (n = 15, mean age = 32 years, work experience = 0.25-29 years) from a South African manufacturing factory using a GMA welding process.…”
Section: Human Immunotoxicity Studiesmentioning
confidence: 99%
“…Some studies have shown that lead increased and decreased the erythrocyte antioxidant enzymes, superoxide dismutase, catalase, and glutathione peroxidase [35][36][37]. A study showed that the activities of the antioxidant enzymes depended on the lead concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have applied urinary isoprostane as biomarkers of oxidative stress in general. The formation of isoprostane is related to personal factors (age) (Dohi et al, 2007), occupational exposure (welding fume) (Han et al, 2005), life style (vitamin C, vitamin E supplementation (Huang et al, 2002), smoking, (Dietrich et al, 2002;Dietrich et al, 2003), vegetable and fruit intake (Thompson et al, 2005), and alcohol consumption (Hartman et al, 2005), and occurrence of chronic diseases (asthma, atherosclerosis, ischemia-reperfusion, cardiovascular disease (Cracowski, 2004), systemic lupus erythematosus, inflammatory rheumatic disease, diabetes mellitus (Cracowski et al, 2002), and breast cancer (Rossner et al, 2006). Il'yasova et al (2004) indicated that ELISA measurements overestimates F2-Isoprostane levels than the GC/MS measurements.…”
Section: Discussionmentioning
confidence: 99%